Evaluation of the Educational Relationship in the University - Mario Rueda Beltrán (Universidad Autónoma de Baja California, 2004)
Educational evaluation processes appeared in Mexico in the late eighties, associated with financing and accreditation to ensure the quality of educational services, according to the official discourse. This article presents a characterization of the processes of evaluation of teaching in universities and of student-opinion questionnaires. It stresses the use of this instrument in the decision to allow academics access to financial incentive programs, and technical carelessness in the instrument's preparation. We point out the paltry amount of connection between evaluation and other activities such as ongoing training, planning and the continuing review of institutional conditions. It suggests developing a critical attitude toward current practices to enable to resolution of problems detected, and to encourage the positive aspects also present. The evaluation of teaching is a social activity imbued with value judgments-in which the actors do not participate with the desired equity.